Project-Based Learning as a Catalyst for Innovation: Analyzing its Role and Effectiveness in Developing Creative Thinking - Gunawan Gunawan; Lovy Herayanti; Ahmadi Ahmadi; Fahmi Yahya; Baiq Nabila Saufika Zainuri (Indonesian Journal of STEM Education, 2023)
This narrative review synthesizes recent literature to explore the significant role of Project-Based Learning (PjBL) as a catalyst for innovation through the development of creative thinking among students. Drawing from a comprehensive review of studies, this paper examines how PBL frameworks, by engaging learners in authentic, complex problem-solving and hands-on project creation, inherently foster environments conducive to divergent thinking, novel idea generation, and critical problem analysis. We analyze the pedagogical mechanisms within PjBL, such as collaboration, inquiry-based learning, and iterative design, that contribute to enhancing students' creative abilities across various educational levels and disciplines, including STEM and engineering. Furthermore, the review discusses the documented effectiveness of PjBL in improving not only creative thinking skills but also related competencies like critical thinking and self-efficacy, which are vital for innovation. The findings underscore PjBL's potential to equip students with the necessary cognitive tools to navigate and contribute creatively to an ever-evolving world. This review aims to consolidate current understanding and highlight future research directions for optimizing PjBL implementation to maximize its impact on fostering innovation-driven creative thinking.